Common Interest and Tolerance: Synergy as a Challenge for Heterogeneous Teams. A Qualitative Study of Six Multicultural Workgroups at University - Brasseur, Martine (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
How can multicultural workgroups achieve synergy and become teams? To answer, we resorted to non-participant observation of six workgroups at university. The data were collected in 41 interviews and 14 meetings. Three types of workgroup were distinguished depending on the scope for individual singularities to assert themselves or for a shared identity to be developed. The principal findings are that a workgroup’s success depends on implementing self-regulation to move from personal to common interests and from toleration to tolerance. This is independent of its heterogeneous/homogeneous composition, which is a matter of perception and varies during the different stages of team-building.